Língua, sujeito e história: implicações da noção de função-autor na produção dicionarística de Caldas Aulete - Siveris, Daiane (2012)
In this paper, the objective is to analyze how the function-author notion works in the prefaces of the Dicionário Contemporâneo da Língua Portuguesa (DCA), by Francisco Júlio Caldas Aulete, published between the years 1881 and 1986. In this research, we considered the dictionary as the object of study and the prefaces of eight editions of the DCA as the corpus of analysis, three Portuguese editions -1881, 1925 and 1948 and five Brazilian editions - 1958, 1964, 1974, 1980 and 1986 - in light of the Discourse Analysis theoretical and methodological principles in consonance with the History of Linguistic Ideas, as they both were conceived in France and as they have been developed in Brazil. The interpretation about the prefaces conducted us to two main points to understand how the function-author works. The first point refers to the linguistic colonization/decolonization in Brazil and the second point relates to the establishment of the dictionaries as memory networks. About the first point, the analysis performed led us to realize that the DCA Portuguese editions lay emphasis on the linguistic unit of the Portuguese language, as it searches for the grammaticalization of a single language, Portuguese language, and the Brazilian editions are determined by diversity; we observed that there is, in some cases, the inclusion of brazilianisms and, in other cases, there is the grammaticalization of a language based on the Brazilian patterns. In this process, the function-author notion in the DCA is highlighted since the elaboration of a dictionary aims also at its constitution, formulation and circulation; the function-author works in these relations, because, in the process of sense constitution, there is the interpellation of the individual into subject, the constitution of its historical form-subject and the effects produced by its subject position in discourse; in the formulation process, there is a relation between the discourse and the text, that upgrades the memory in presence, the subject individuation by its function-author; in the circulation, there is the functioning of the enunciation circumstances and the social subjects that assume the function-author in their routes, in different places, whether in Portugal or in Brazil. Furthermore, the dictionaries establishment into memory networks, where a dictionary refers to others already published, also determines the functioning of the function-author notion, as other and new linguistic tools are being constituted and published, other and new are the subject positions. This is due to the different discourses that circulate in society, the different production conditions of these discourses, as well as the way the subject means himself and his own language.